Solid pseudopapillary tumor of the pancreas (Frantz tumor) in a 13-year-old girl - Resio, Nicolás P.; Ducás, Álvaro; Manuel, Nadia; Padin, Guillermina; Díaz Pietrini, Magdalena; Pomar, Pablo (Revista Argentina de Cirugía, 2026)
Solid pseudopapillary tumor (SPT) of the pancreas is a rare neoplasm with a low malignant potential and represents 1- 3% of all pancreatic tumors. They usually occur in women and are the most common solid pancreatic tumor in children. A 13-year-old girl visited the emergency department due to abdominal pain in the right hypochondrium radiating to the back, nausea and vomiting lasting 5 days. A SPT was diagnosed by ultrasound, computed tomography (CT) scan and magnetic resonance imaging (MRI). The patient underwent cephalic pancreaticoduodenectomy and was discharged. The pathological study reported a SPT of the pancreas. The surgical approach of these tumors through open surgery or laparoscopy offers excellent long-term survival.